Analysis of Grade II Burns Healing from Andaliman Fruit Ethanol Extract Ointment (Zanthoxylum Acanthopodium Dc.) in Wistar Rats (Rattus Norvegicus) - Li Sha; Florenly Florenly; Johannes Bastira Ginting; Fioni Fioni (Budapest International Research and Critics University, 2021)
The prevalence of injuries has increased every year, from riskesdas results data in 2013 reported that burns are the sixth cause of accidental injuries with a prevalence of 0.7 percent of the Indonesian population. Andaliman fruit extract with various phytochemicals has active physiological activity as a potential antioxidant and antimicrobial. The study aims to explore the wound healing effects of andaliman fruit ethanol extract. This study was an experimental study using 20 rats divided into 4 groups (Control, Standard, Essential Oil 10%, and Essential Oil 15%). Wound healing parameters are assessed through wound contraction and epithelial period. Samples of andaliman fruit used in this study were obtained from one of the traditional markets in the city of Medan. Essential oils are obtained from the hydrodistillation process. The results of the study showed significant differences in the epithelial period of the standard group, 10% and 15% in the control group. However, in the andaliman ointment group and the standard group, there was no difference in the epithelial period. This is evident from the value P < 0.05 (Value P = 0.029). The conclusion of the healing effects of burns possessed by andaliman ointment both 10% and 15% and nebacetin ointment as standard shows a significant difference. Where the wound contraction rate of your ointment is 15% better than nebacetin ointment as standard. But in both andaliman ointments, both 10% and 15% and nebacetin ointment as standard did not show significant differences in the parameters of the epithelial period.